(untitled) (Kinesiology, 2022)
We aim to investigate the impact of variable soccer pitch sizes on the position of players during unbalanced small-sided games (SSGs) and compare the responses of players from two different age groups. Forty-eight young players (n = 24 under-13 and n = 24 under-14) took part in the study and played 3 vs. 3 + 1 SSGs on two different pitch sizes (smaller: 36 x 27 m / 139m2 per player; and larger: 40 x 29 m / 166 m2 per player). Players’ positions on the pitch (length, width, length-to-width ratio, stretching index, and spatial exploration index) were assessed by the positional data provided by global position system devices and were compared within age groups and between game formats using a two-way analysis of variance. Results showed higher values of spatial exploration index (SEI) in the larger SSGs than in the smaller format (p<.001). Moreover, a higher length (p<0.001) and length-to-width ratio (p<.001) was observed in the younger group. Finally, the larger format presented higher values of SEI and stretching index, independent of the age group (p<.001). In the smaller format, U-14 players presented a higher stretching index, while in the larger format U-13 players presented higher values in the same variable. We conclude that enlarging the pitch size constrains players’ behaviour during SSGs, and older players are more able to deal with this more complex task context than younger ones. Key words: football, performance, positional analysis, task constraints, small-sided games